Transcriptomic Analysis Reveals Key Genes Related to Betalain Biosynthesis in Pulp Coloration of Hylocereus polyrhizus - Qingzhu, Hua; Chengjie, Chen; Zhe, Chen; Pengkun, Chen; Yuewen, Ma; Jingyu, Wu; Jian, Zheng; Guibing, Hu; Jietang, Zhao; Yonghua, Qin (Frontiers in Plant Science, 2016)
Betalains have high nutritional value and bioactivities. Red pulp pitaya (Hylocereus polyrhizus) is the only fruit containing abundant betalains for consumer. However, no information is available about genes involved in betalain biosynthesis in H. polyrhizus. Herein, two cDNA libraries of pitaya pulps with two different coloration stages (white and red pulp stages) of Guanhuahong (H. polyrhizus) were constructed. A total of about 12 Gb raw RNA-Seq data was generated and was de novo assembled into 122,677 transcripts with an average length of 1,183 bp and an N50 value of 2008. Approximately 99.99% of all transcripts were annotated based on seven public databases. A total of 8,871 transcripts were significantly regulated. Thirty-three candidate transcripts related to betalain biosynthesis were obtained from the transcriptome data. Transcripts encoding enzymes involved in betalain biosynthesis were analyzed using RT-qPCR at the whole pulp coloration stages of H. Polyrhizus (7-1) and H. Undatus (132-4). Nine key transcripts of betalain biosynthesis were identified. They were assigned to four kinds of genes in betalain biosynthetic pathway, including tyrosinase, 4, 5-DOPA dioxygenase extradiol, cytochrome P450 and glucosyltransferase. Ultimately, a preliminary betalain biosynthetic pathway for pitaya was proposed based on betalain analyses and gene expression profiles.